2019
DOI: 10.1093/brain/awz126
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative facial expression analysis revealed the efficacy and time course of oxytocin in autism

Abstract: Discrepancies in efficacy between single-dose and repeated administration of oxytocin for autism spectrum disorder have led researchers to hypothesize that time-course changes in efficacy are induced by repeated administrations of the peptide hormone. However, repeatable, objective, and quantitative measurement of autism spectrum disorder’s core symptoms are lacking, making it difficult to examine potential time-course changes in efficacy. We tested this hypothesis using repeatable, objective, and quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Although the bene cial effects of single-dose oxytocin on measures of ASD core symptoms have been consistently reported across studies (3)(4)(5)(6)(7)(8), previous studies on the repeated administration of oxytocin have reported inconsistent ndings, impeding further development of oxytocin as an approved medication (9). Recently, we found a progressive deterioration in the e cacy of oxytocin (10,11), and proposed that this phenomenon may account for the reported inconsistencies in the effect of repeated administration. Elucidating the mechanisms underlying the time-course change in the e cacy of repeated oxytocin administration may help advance the development of oxytocin-based therapy for ASD core symptoms.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Although the bene cial effects of single-dose oxytocin on measures of ASD core symptoms have been consistently reported across studies (3)(4)(5)(6)(7)(8), previous studies on the repeated administration of oxytocin have reported inconsistent ndings, impeding further development of oxytocin as an approved medication (9). Recently, we found a progressive deterioration in the e cacy of oxytocin (10,11), and proposed that this phenomenon may account for the reported inconsistencies in the effect of repeated administration. Elucidating the mechanisms underlying the time-course change in the e cacy of repeated oxytocin administration may help advance the development of oxytocin-based therapy for ASD core symptoms.…”
Section: Introductionmentioning
confidence: 80%
“…The trial sites were the University of Tokyo Hospital, Nagoya University Hospital, Kanazawa University Hospital, and University of Fukui Hospital in Japan (UMIN000015264) (14). The details of this trial are described elsewhere (11,14). Brie y, the inclusion criteria of this trial were as follows: (1) 18-54 years of age; (2) male; (3) diagnosis of autistic disorder, Asperger's disorder, or pervasive developmental disorders not otherwise speci ed (PDD-NOS) based on DSM-IV-TR; (4) score exceeding the cut-off value (i.e.…”
Section: Experimental Design and Participantsmentioning
confidence: 99%
See 3 more Smart Citations